Application of Simultaneous Inversion Characterizing Reservoir Properties in X Field, Sabah Basin - Ming Xiang, L. (Institute of Physics Publishing, 2017)
X field located between the East Baram Delta and Southern Inboard Belt, which is elongated northwest to southeast direction in Middle Miocene Sabah Basin. Previous studies were unable to differentiate the lithology and fluid distribution in the field by using conventional reservoir characterization approaches for example amplitude versus offset (AVO) analysis and post-stack deterministic inversion due to the low contrast in P-impedance between gas sand and shale. Thus, the goal of this approach is to obtain a reliable estimation of P wave velocity (VP). S-wave velocity (Vs), and density (). From these parameters, we predict the fluid and lithology properties for better reservoir characterization. A feasibility analysis was conducted and the results show that prediction of the hydrocarbon reservoir in X field is feasible using P-impedance and Vp/Vs. Consequently, the simultaneous inversion is carried out to derive the rock properties such as density, P-impedance, S-impedance, Lambda-rho (λ) (Incompressibility), and Mu-rho (μ) (Rigidity). The results from this study demonstrate the effectiveness of simultaneous inversion and the best parameters for enhancing the resolution and characterizing the hydrocarbon sand layer of the prospect. © Published under licence by IOP Publishing Ltd.